Моделирование работы асинхронного двигателя в частотном электроприводе при различных настройках преобразователя - Петрушин, Виктор Сергеевич; Якимец, Андрей Миронович (НТУ "ХПИ", 2010)
In result of simulation of induction motor fed frequency converter the mechanical and regulation characteristics are got at the different tunings of frequency converter.
The modeling of induction motor in frequency electric drive at the different tunings of converter
Keywords: нагрузка; регулирование частотное; напряжение бустерное; обмотка ротора; модуляция широтно-импульсная; сопротивление активное